Tracing carbon emissions convergence along the way to participate in global value chains: A spatial econometric approach for emerging market countries - Cai, Yuting; Qian, Xinze; Nadeem, Muhammad; Wang, Zilong; Lian, Tao; Haq, Shamsheer Ul (Frontiers in Environmental Science, 2022)
The proliferation of trade agreements has offered a viable framework for the economic and trade integration of many nations. Additionally, the growth and expansion of global value chains has increased prospects for knowledge and technological spillovers as well as the potential for production method convergence. This might have possible effects on the environment in both developed and developing nations. The objective of this study is to determine whether participation in global value chains (GVCs) can serve as a foundation for the convergence of carbon emission across nations. Spatial panel data econometrics is used to examine data from 22 emerging economies between 1995 and 2019 in order to provide an answer. The findings support the global value chains-based conditional carbon convergence of the countries and show a spatial link between global value chains participation and CO2 growth. Furthermore, results show that increasing global value chains participation with other variables; both directly and indirectly, via spillover effects, encourages closing the CO2 emission gap across nations. The findings show that global value chains may be able to increase how successful carbon efficiency initiatives are. Therefore, when developing environmental legislation, many aspects of global value chains participation and their advantages should be considered.